Penerapan Metode Problem Solving Terbimbing Untuk Meningkatkan Aktivitas dan Hasil Belajar Kimia Pada Materi Hukum-Hukum Dasar Kimia di SMA Negeri 1 Tompaso - Nathalia F. C. Bambulu; I Dewe Ketut Anom (Oxygenius Journal Of Chemistry Education, 2022)
This research aims to increase learning activities and learning outcomes through the application of problem solving methods guided to the basic laws of chemistry class X Mia. This study was conducted in class X sma Negeri 1 Tompaso with a sample number of 20 people. This study is a Class Action Research consisting of 2 cycles. Each cycle includes 4 stages, namely planning, implementation, documentation observation, tests and questionnaires. Data analysis uses descriptive methods. The results showed that the application of guided problem solving methods can increase learning activity (from 64% in cycle 1 to 85% in cycle II) as well as affective aspects (from 68.16% to 75.44%) in the basic laws of chemistry class X Mia Sma Negeri 1 Tompaso school year 2018/2019.